Gambaran Coping Stres Pada Perempuan Dewasa Awal Yang Bersinggungan Dengan Hukum - Muquita Mahenda; Dwi Cahya, Nabila Aulia; Sasi, Kezia Btari; Basaria, Debora (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
This study aims to describe the stress coping strategies of early adult women at the Class IIA Women’s Correctional Facility in Jakarta. A total of 180 incarcerated individuals aged 20–40 years participated in this descriptive quantitative study using purposive sampling. Data were collected using the Indonesian version of the Ways of Coping Questionnaire-Revised (WOC-R), consisting of 66 items across eight coping dimensions. Results showed that the most frequently used coping strategy was Positive Reappraisal (M = 3.28), followed by Planful Problem Solving (M = 3.26) and Confrontive Coping (M = 2.85). A total of 74 participants (41.1%) reported using Confrontive Coping very frequently, indicating an active and direct approach to stress management. Adequate internal consistency was found only in Positive Reappraisal (? = 0.751) and Planful Problem Solving (? = 0.721). These findings suggest that emotion-focused coping—particularly positive reframing—along with problem-solving approaches, are dominant strategies used by incarcerated women to adapt to the stressful prison environment. Keywords: stress coping, early adult women, inmates, correctional facility, WOC-R